On bounded truth-table and positive degrees - Ditchev, Angel (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 1994)
In the present paper it is shown that there exists a recuraively enurable btt-degree containing an infinite anti-chain of recursively enurable $p$-degree.